Analysis of sleep duration, energy intakes, physical activity, and metabolic syndrome based on the presence or absence of obesity and hypertension in working Korean adults - Sung, Eunsook; Lee, Youngjun; Kim, Sanghoo; Park, Jonghoon (Frontiers in Public Health, 2025)
BackgroundMetabolic syndrome poses a serious public health concern among working adults, especially in the context of increasing rates of obesity and hypertension. These lifestyle-related conditions are intricately linked to sleep patterns, dietary behaviors, and physical activity.ObjectiveThis study aimed to examine how sleep duration, energy intake, and physical activity levels—key lifestyle factors—are associated with metabolic syndrome based on the presence or absence of obesity and hypertension among working Korean adults.MethodsWe analyzed 6,503 working Korean adults aged 20–59 years using cross-sectional data from the Korea National Health and Nutrition Examination Survey covering 2016–2018. This study divided the participants based on their obesity and hypertension status. We assessed the participants’ sleep duration on weekdays and weekends, their total dietary energy consumption and macronutrient intake using a 24-h dietary recall method conducted by trained interviewers, and occupational and recreational physical activities, and movement levels in MET min/week. We evaluated metabolic syndrome components using standard criteria and examined between-group differences using two-way analysis of variance and Bonferroni post-hoc tests.ResultsIndividuals with hypertension had significantly shorter weekday sleep (p < 0.05) and weekend sleep durations (p < 0.001) than those without. The highest total energy intake was significantly higher in obese individuals with hypertension than in those without hypertension (p < 0.05) and non-obese individuals with hypertension (p < 0.001). Furthermore, obese individuals with hypertension showed higher levels of occupational vigorous and total physical activities than those without hypertension (p < 0.01 and p < 0.001, respectively), whereas no difference was observed between obese and non-obese individuals with hypertension.ConclusionThis study concludes that hypertension and obesity may reinforce each other through reduced sleep duration, lower physical activity levels, and increased energy intake, thereby exacerbating metabolic syndrome. To prevent metabolic syndrome in working adults, multiple aspects of sleep, nutrition, and physical activity that match their unique risk profiles must be considered.